Peran Etika Kerja Islam dalam Meningkatkan Kinerja Karyawan Perbankan Syariah - AL - AZAHRO, SHAKINAH BINTI (Maliki Interdisciplinary Journal, 2026)
This study aims to identify the influence of Islamic work ethics on human resource performance in Islamic financial institutions. Islamic work ethics are considered a crucial foundation that distinguishes Islamic banking from traditional banking, as they are guided by values ​​found in the Qur'an and Sunnah, such as honesty, responsibility, fairness, hard work, and mutual assistance. Numerous findings from previous studies indicate that Islamic work ethics have a positive and significant influence on employee performance in many aspects, such as quality, quantity, punctuality, effectiveness, and independence in work. Islamic work ethics motivate employees to view work as a form of worship, which in turn increases their contribution to the organization or company. Furthermore, Islamic work ethics also play a significant role in strengthening employee commitment and optimal work behavior in Islamic banking institutions. Therefore, consistent implementation of Islamic work ethics is crucial to improving employee performance and ensuring the sustainability of Islamic banking.